RIPPLE OF AGONY - Jennifer Gracia (Kata Kita: Journal of Language, Literature, and Teaching, 2017)
The creative project I had written is a novel that is telling the story of a man named, Arya, who seems to be a good man while actually he has a very dark secret and past. He loves to hunt for girl in cafés and he later will do whatever he needs to do in captivating the girl’s heart. When he gets the girl’s heart and trust, he will do what he wants the most, the main purpose of his hunting which is overpowering the girl. In this story, I choose to write about the life of a serial rapist with the theme of love changes everything. It helps me in realizing my aim for writing this work which is to raise more awareness towards the cases of rape that happen around us. In rape cases, the victim is being sympathized while the criminal is being hated. While actually, the criminal also needs support from his surrounding in order to be a better man in the future. What I am trying to say is that we should hate his act, but not the person. In the story, Arya will see how people hate him even after he serves the fifteen years charges and willing to be a better person. As for the genre, I choose realistic fiction in order to make the story believable since it is written based on the research with the main character created according to the characteristic of serial rapist in real life.